MEDIATION IN COMMERCIAL COURT AS EQUAL PROTECTION BETWEEN DEBTORS AND CREDITORS - Zulaeha, Mulyani (Lambung Mangkurat Law Journal, 2017)
Mediation as a way of dispute resolution through negotiation process toachieve agreement of the parties assisted by mediator. It is considered as a form ofdispute resolution that can meet the parties’ wishes, reducing the time and cost. It wantsa dispute was resolved through the peace of the parties as outlined in the agreement.Moving from the weakness of peace as contained in Act No. 37/2004, then themediation empowerment in the Commercial Court as a breakthrough and steps takento create an equal protection between debtors and creditors (especially prospectivedebtors). The empowerment of mediation in the Commercial Court is in line withthe policy direction and strategy of legal development contained in PresidentialRegulation No. 2/2015, especially civil law enforcement, namely the resolution ofcivil cases is performed by encouraging the optimization of mediation process in courtand simplification of civil procedure is expected to encourage the efficiency of civilresolution and give positive contribution to the improvement of national economy.